Isolation and molecular characterization of some pathogenic skin bacteria - الدالي, حسن; أميمة ناصر; عماد حداد; تميم حماد (Latakia University Journal -Medical Sciences Series, 2024)
Three types of skin bacteria were isolated and profiled from pathological samples received at Tishreen University Hospital in Lattakia Governorate during the period from (1/4-1/10/2022), and the bacterial isolates were distinguished by some characteristics based on their staining by the Gram method, and according to the color characteristics on the Specific and selective cultures, some biochemical properties and PCR technology. The results showed the isolation of two types of cocci, and these isolates are (A) Staphylococcus aureus type and (B) Staphylococcus epidermidis, Gram-positive and type (C) Pseudomonas aeruginosa, Gram-negative, during an incubation period that lasted (24-72) hours. And that at a temperature of (37) °C.